Fans for diversity? A Critical Race Theory analysis of Black, Asian and Minority Ethnic (BAME) supporters' experiences of football fandom. Issue 4 (2nd October 2019) - Lawrence, Stefan; Davis, Christian
ABSTRACT: Over the last 20 years or so there has been a proliferation of anti-racist organisations, campaigns and interventions across football at all levels, allied to broader social, cultural and political shifts in late modern digital societies. Indeed, relying on certain statistical data, which reports a decline in racist incidents in stadia, might lead many anti-racist policymakers to champion liberal doctrines and to proclaim football fan cultures as quantitatively 'less racist'. However, in this article, using Critical Race Theory as a guiding theoretical framework, throughout, we foreground the qualitative experiences and stories of BAME football fans to understand why football fandom and spectatorship remain predominantly 'White' activities. Using semi-structured interviews and observational techniques, we explore critically the continued significance of 'race' as a mediating factor in football fandom, how BAME football fans negotiate-resist belonging in football fandom cultures and the implications of BAME fans' testimonies for policymakers. We conclude by arguing for an increase in intersectional research across football/football fan studies, to understand better the racialised aspects of football fandom, and we also urge scholars and policymakers, alike, to place greater emphasis on 'trust building' innovations, as opposed to 'diversity', given the latter has taken on a commercial value of late.